Dukungan Sosial Memengaruhi Tingkat Stres Perawat Selama Pandemi Covid-19 : Social Support Affects the Level of Stress in Nurses During the Covid-19 Pandemic - Maijefri, Ozi; Rizal, Ahmad; Lanasari (Journal of Nursing Education and Practice, 2022)
Introduction: Nurses as medical personnel who are directly involved in handling Covid-19 patients are very at risk of experiencing stress. Social support plays an important role in dealing with nurse stress. Objectives: to find out the relationship between Social Support and Stress Levels During the Covid-19 Pandemic at PMI Bogor in 2021. Method: This type of research is a quantitative descriptive with a cross sectional approach. The sampling technique used was Total Sampling with a total of 78 respondents. The instrument used is a questionnaire sheet. Analysis of this research using Somer's D test with = 0.05. Result: From the results of univariate data testing, the majority of early adults (26-35 years) were 49 people (63%), with female sex as many as 49 people (62.8%), the majority experienced moderate stress levels as many as 54 people (69.2% ) and have moderate social support as many as 55 people (70.5%). From the results of the bivariate analysis test using the Somers'D test, a p-value of 0.000 (p <0.05) was obtained with a contingency coefficient of 0.720 (0.60 - 0.799). Conclusion: There is a significant relationship between social support and nurses' stress levels during the Covid-19 pandemic with the strength between variables at a strong level.